STRATEGIES FOR COPING WITH LANGUAGE ANXIETY IN ORAL PRESENTATION - Siti Nurulita Azizah; Yupika Maryansyah; Dian Susyla; Ririn Putri Ananda (Universitas Negeri Manado, 2023)
This study aims to find out and describe the strategies students used for coping with language anxiety in oral presentation and to find out the most dominant strategy used by students for coping with language anxiety in oral presentation. This research used a descriptive qualitative research method. The subject of this research were 6th semester students of English Study Program of Muhammadiyah University of Bengkulu. 22 English students who had do presentation in the class. Researcher used observation sheet, questionnaire and interview guide to data collection technique. The result of this study showed that; 1) students used 5 strategies for coping their language anxiety were preparation, relaxation, positive thinking, peer seeking and resignation; 2) the dominant strategy used by students were preparation and relaxation. The conclusion of this study are students used 5 strategies for coping their language anxiety and students used dominant strategy for coping their language anxiety with preparation.